Framing the Risk of Islamic Based Equity Financing: an Inside Look - Wiwiek Rabiatul Adawiyah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This article is a review of the literature that aims at bringing into surface the issue of risk management in equity-based financing which is currently less attractive to Islamic banks. There are several forms of Islamic financing offered to potential borrower. Equity financing is less favorable as compared to debt financing due to high risks associated with it. Substantial numbers of strategies have been developed by researchers to mitigate the financing risks nonetheless the attempt is far from succeed. It is evidenced in the literature that both investors and financial intermediaries tend to overlooked profit and loss sharing mode of financing. Meanwhile Equity financing is adored to be the best form of financing to be offered to small business since it is operating under the principle of justice. Profit and loss sharing mechanism relieve both fund providers and borrowers from financial burden. This article shall review potential risks embedded in equity financing and strategies to overcome the problem.